1989
DOI: 10.1210/endo-125-1-275
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Regulates Parathyroid Hormone Messenger Ribonucleic Acid (mRNA), but not Calcitonin mRNAin Vivoin the Rat. Dominant Role of 1,25-Dihydroxyvitamin D*

Abstract: In vivo 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) decreased PTH and calcitonin gene transcription. A low calcium is the major signal for PTH secretion, and a high calcium for calcitonin secretion. We report here that calcium has no effect on calcitonin messenger RNA (mRNA) levels in vivo in the rat, but that a low calcium markedly stimulates PTH mRNA levels. Serum calcium was decreased by ip phosphorus and increased by calcium gluconate (ip or iv infusion) and demonstrated that a low serum calcium markedly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 0 publications
3
37
0
1
Order By: Relevance
“…Calcium not only determines PTH secretion but also regulates PTH gene expression both in vitro (1,2) and in vivo (3,4). Calcitonin, on the other hand, is secreted in response to a high calcium but its transcription is not affected by calcium (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium not only determines PTH secretion but also regulates PTH gene expression both in vitro (1,2) and in vivo (3,4). Calcitonin, on the other hand, is secreted in response to a high calcium but its transcription is not affected by calcium (4).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium not only determines PTH secretion but also regulates PTH gene expression both in vitro (1,2) and in vivo (3,4). Calcitonin, on the other hand, is secreted in response to a high calcium but its transcription is not affected by calcium (4). The transcription of both PTH and calcitonin genes is markedly reduced by 1,25(OH)2D3 both in vitro (5)(6)(7) and in vivo (8,9), suggesting a central role for 1,25(OH)2D3 in orchestrating calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Tomlinson et al (24) showed that the urinary cAMP response to PTH is blunted in patients with HPT and that this phenomenon tends to occur in patients with high endogenous PTH concentrations. Because 1,25(OH) 2 D is required to correct skeletal resistance to the calcemic action of PTH (25), and it inhibits synthesis and secretion of PTH in vitro and in vivo (26,27), reduced 1,25(OH) 2 D promotes proliferation of the parathyroid glands, resulting in a vicious cycle of HPT. We found an increased frequency of multiglandular disease in the renal insufficiency group.…”
Section: Discussionmentioning
confidence: 99%
“…The PTH gene's expression is also regulated by calcium, where the major effect is that ofa low calcium increasing PTHmRNA levels in vivo (2, 7). In contrast, calcitonin gene expression is not regulated by calcium in vivo (7). At the level of secretion, calcium is the major regulator for both PTH, and calcitonin, with a low calcium being the secretagogue for PTH, and a high calcium for calcitonin.…”
Section: Introductionmentioning
confidence: 98%